Effects of complex whole-body movements on EEG activity: a scoping review - Müller, Gabriel; Salem, Atef; Schöllhorn, Wolfgang I. (Frontiers in Psychology, 2025)
IntroductionTo understand brain function, diverse approaches are pursued. The influence of movements on brain activity has been part of this research for decades. Recent advancements in electroencephalography (EEG) coupled with a shift in focus toward the effects of complex whole-body movements provided additional inspirations in this area. The investigation of the effects of endurance sports on brain activity poses the problem that an increase in EEG activity does not allow a differentiation between the effects caused by an increase in metabolism and those caused by an increase in the coordinative demands that must be coped with in parallel. This issue is currently being increasingly investigated using movements in which metabolism is not increased accordingly. This scoping review aims to summarize studies that investigated the acute effects of complex whole-body movements with increased parallel information processing on electrical brain activity to identify trends and potential issues that can be considered for future research.MethodsA comprehensive search across five scientific databases (PubMed, Web of Science, Scopus, SPORTDiscus, ProQuest) was conducted for studies that examined the acute effects of complex movements on EEG activity. The quality of the studies was assessed using a combination of the Quality Assessment Tool for Quantitative Studies (QATQS) and a modified quality assessment tool to evaluate EEG data acquisition and analysis.ResultsThirteen studies met the inclusion criteria for our scoping review, showing considerable heterogeneity in terms of design and type of movement. Nevertheless, the findings revealed a trend toward increased theta and alpha activity in frontal, central, and parietal areas during and after movement. In other frequency bands the findings were not consistent.DiscussionThese findings are discussed in the context of possible moderating factors. Based on a consistent EEG methodology, future research should increasingly investigate the complexity of movements with regard to a clearer differentiation of cognitive demands to identify these as potential moderator variables.